Microglia Pyroptosis: A Candidate Target for Neurological Diseases Treatment - Wu, Xian; Wan, Teng; Gao, Xiaoyu; Fu, Mingyuan; Duan, Yunfeng; Shen, Xiangru; Guo, Weiming (Frontiers in Neuroscience, 2022)
In addition to its profound implications in the fight against cancer, pyroptosis have important role in the regulation of neuronal injury. Microglia are not only central members of the immune regulation of the central nervous system (CNS), but are also involved in the development and homeostatic maintenance of the nervous system. Under various pathological overstimulation, microglia pyroptosis contributes to the massive release of intracellular inflammatory mediators leading to neuroinflammation and ultimately to neuronal damages. In addition, microglia pyroptosis lead to further neurological damage by decreasing the ability to cleanse harmful substances. The pathogenic roles of microglia in a variety of CNS diseases such as neurodegenerative diseases, stroke, multiple sclerosis and depression, and many other neurological disorders have been gradually unveiled. In the context of different neurological disorders, inhibition of microglia pyroptosis by targeting NOD-like receptor family pyrin domain containing (NLRP) 3, caspase-1 and gasdermins (GSDMs) by various chemical agents as well as natural products significantly improve the symptoms or outcome in animal models. This study will provide new ideas for immunomodulatory treatment of CNS diseases.